Genome-wide binding of transcription factors in inv(16) acute myeloid leukemia - A. Mandoli; K. Prange; J.H.A. Martens (Genomics Data, 2014)
The inv(16) translocation is associated with 5% of AML cases and gives rise to expression of the oncofusion protein CBFβ-MYH11. Although different molecular mechanisms for the oncogenic activity of this fusion protein have been proposed these were mostly based on in vitro experiments or single loci analysis. Recently, we investigated the genome-wide action of this fusion protein in the context of other hematopoietic transcription factors (Mandoli et al., 2014). Here, we describe in detail the ChIP-seq and RNA-seq methods used to generate the data associated with this study. Our analysis of CBFβ-MYH11 as well as multiple other hematopoietic transcription factors using ChIP-seq data revealed RUNX1 dependent binding of CBFβ-MYH11 as well as interaction of the RUNX1/CBFβ-MYH11 complex with other hematopoietic regulators. Further RNA-seq based analysis suggested that CBFβ-MYH11 can act both as activator and repressor.